Kajian Modifikasi terhadap Karakteristik Fisik TepungTermodifikasi Anneling: Kajian Pustaka - Rahayu, Marni; Wahyuni, Sri; Sadimantara, Muhammad Syukri (Jurnal Sains dan Teknologi Pangan, 2020)
ABSTRACT Review this aims to determine the effect of temperature and heating time on physical characteristics such as swelling power, IKA (Water Solubility Index), and viscosity of the flour that was physically modified by the resulting anneling method. The modification process can be done in several ways, including the temperature above the gelatinization and the temperature below the gelatinization. Anneling modified flour has the potential to substitute wheat flour in food processing, thereby reducing food dependence on wheat.Based on the results of the review, it can be seen that the sweet potato flour, breadfruit and modified white millet using the annealing method produce moisture content that is in accordance with the SNI standard for flour, namely 2,51%, 9,12%, and 7,95%, respectively. The physicochemical characteristics of several types of modified flour using annealing method, namely sorghum flour has a viscosity of 465,04 cP, swelling power of 9,24 g / g, and solubility of 4,20%. Breadfruit flour has a viscosity of 14,33 cP, a swelling power of 10,34 g / g, and a solubility of 23,99% and white millet flour has a viscosity of 3260,33 cP, a swelling power of 7,14 g / g, and a solubility of 13,53%. Keywords: Flour, Annealing, Characteristics. ABSTRAKReview ini bertujuan untuk mengetahui pengaruh suhu dan lama pemanasan terhadap karakteristik fisik seperti swelling power, IKA (Indeks Kelarutan dalam Air), dan viskositas pada tepung yang dimodifikasi secara fisik dengan metode anneling yang dihasilkan. Proses modifikasi dapat dilakukan melalui beberapa cara diantaranya adalah dengan suhu diatas gelatinisasi dan suhu dibawah gelatinisasi. Tepung termodifikasiannealing memiliki potensi untuk mensubtitusi tepung terigu pada pengolahan pangan sehingga mengurangi ketergantungan pangan terhadap terigu.Berdasarkan hasil review dapat diketahui bahwa tepung ubi jalar, sukun dan millet putih modifikasi menggunakan metode annealing menghasilkan kadar air yang telah sesuai standar SNI  tepung yaitu berturut-turut 2,51%,  9,12%, dan 7,95%.  Karakterisitik fisikokimia beberapa jenis tepung termodifikasi menggunakan metode annealing  yaitu tepung sorghum memiliki viskositas 465,04 cP, swelling power 9,24 g/g, dan solubility 4,20%.  Tepung sukun memiliki viskositas 14,33  cP, swelling power 10,34 g/g, dan solubility 23,99% dan tepung millet putih memiliki viskositas 3260,33  cP, swelling power 7,14 g/g, dan solubility 13,53%  Kata kunci: Tepung,Annealing, karakteristik.